Effect Of Digital Marketing And Social Media On Purchase Intention Of Smes Food Products - et.al, Heri Erlangga (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Marketing is an important part of the management of a company in order to achieve success in achieving company goals. This study aims to determine the influence of social media-based digital marketing on purchasing decisions for SMEs products. The study was conducted in Banten Province by taking a total sample of 210 respondents with a sample of using random sampling technique. Data collection through observation and questionnaires. The data analysis technique was performed using simple linear regression analysis with SPSS software. Based on the results of the research and discussion above, it can be concluded that social media marketing has a significant influence on purchasing decisions on SMEs products. Overall there is a positive influence between social media marketing variables and SMEs product purchasing decisions.